2023
DOI: 10.1039/d3cp03651k
|View full text |Cite
|
Sign up to set email alerts
|

Ligand binding affinity prediction with fusion of graph neural networks and 3D structure-based complex graph

Lina Dong,
Shuai Shi,
Xiaoyang Qu
et al.

Abstract: Accurate prediction of protein-ligand binding affinity is pivotal for drug design and discovery. Here, we proposed a novel deep fusion graph neural networks framework named FGNN to learn the protein−ligand...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 84 publications
1
2
0
Order By: Relevance
“…Building on this, subsequent studies have integrated both refined and general datasets. 54,109,110,128,141 Consistently with the previous results on the positive data in structure-based deep learning, Francoeur et al 54 observed a notable performance boost in a 3D-CNN model when incorporating the general set. They also included the near-native structures obtained by redocking initialized ligand structures via universal force field (UFF), 142 as positive data.…”
Section: Data Augmentation Strategiessupporting
confidence: 74%
See 1 more Smart Citation
“…Building on this, subsequent studies have integrated both refined and general datasets. 54,109,110,128,141 Consistently with the previous results on the positive data in structure-based deep learning, Francoeur et al 54 observed a notable performance boost in a 3D-CNN model when incorporating the general set. They also included the near-native structures obtained by redocking initialized ligand structures via universal force field (UFF), 142 as positive data.…”
Section: Data Augmentation Strategiessupporting
confidence: 74%
“…Updated features from every set of edges are then gathered to predict PLI. While other works employed a single architecture, Dong et al 110 proposed FGNN that fused two different 3D-GNN architectures in an ensemble manner. They highlighted that their strategy could improve the prediction performance on diverse datasets in terms of the expressive power of the model.…”
Section: Notementioning
confidence: 99%
“…Table 3 shows the results of various models on the PDBbind2016 core set, including benchmarks: Fast, DLSSAffinity and FGNN3. 46 The data in the table comes from the optimal model trained with multiple random seeds. It can be found from the table that compared with Pocket_net (no virtual node) which only uses pocket information, SadNet benefits from mid-term virtual node fusion and late stacking fusion to obtain global sequence representation, and the model performance is significantly improved.…”
Section: Resultsmentioning
confidence: 99%